Penguatan Ketahanan Remaja Terhadap Kekerasan Seksual Melalui Pendidikan Seksualitas Pada Siswa Pattanakansuksa Foundation School, Satun-Thailand. - Wiwin Muchtar Wiyono; Eti Mul Erowati; Elisabet Pudyastiwi (Universitas Wijayakusuma Purwokerto, 2026)
Abstract . This outreach program aims to explore the effectiveness of legal outreach in strengthening adolescent resilience against sexual violence through sexuality education at Pattanakansuksa Foundation School, Satun, Thailand. With the rise in cases of sexual violence among adolescents, providing adequate knowledge regarding legal rights and comprehensive sexuality education is crucial. The outreach program aimed to explore students' understanding of sexual violence and appropriate legal responses. The outreach program's results indicate that a legal outreach program integrated with sexuality education significantly increased adolescents' awareness and resilience against sexual violence. Students demonstrated increased knowledge regarding personal boundaries, legal rights, and self-protection strategies. This activity underscores the importance of integrating legal and sexuality education into the school curriculum to build a more resilient generation against sexual violence. Keywords: Legal outreach, adolescent resilience, sexual violence, sexuality education, Pattanakansuksa Foundation School, Thailand.